2003
DOI: 10.1124/jpet.103.054866
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic CYP2B6 Expression: Gender and Ethnic Differences and Relationship toCYP2B6Genotype and CAR (Constitutive Androstane Receptor) Expression

Abstract: CYP2B6 metabolizes many drugs, and its expression varies greatly. CYP2B6 genotype-phenotype associations were determined using human livers that were biochemically phenotyped for CYP2B6 (mRNA, protein, and CYP2B6 activity), and genotyped for CYP2B6 coding and 5Ј-flanking regions. CYP2B6 expression differed significantly between sexes. Females had higher amounts of CYP2B6 mRNA (3.9-fold, P Ͻ 0.001), protein (1.7-fold, P Ͻ 0.009), and activity (1.6-fold, P Ͻ 0.05) than did male subjects. Furthermore, 7.1% of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
345
4
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(373 citation statements)
references
References 32 publications
22
345
4
2
Order By: Relevance
“…Hepatic CYP2B6, whose substrates include the alkylating agents cyclophosphamide and ifosfamide, is expressed differently between the sexes. 19 Significantly higher amounts of CYP2B6 mRNA protein and enzyme activity were found in females than in males. As a consequence some agents will be more effective in females and may, at the same time, show more toxicity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Hepatic CYP2B6, whose substrates include the alkylating agents cyclophosphamide and ifosfamide, is expressed differently between the sexes. 19 Significantly higher amounts of CYP2B6 mRNA protein and enzyme activity were found in females than in males. As a consequence some agents will be more effective in females and may, at the same time, show more toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…As a consequence some agents will be more effective in females and may, at the same time, show more toxicity. 18,19 It is of interest that in our trials women responded significantly better than men (Table 2) although they experienced more toxicity, particularly gastro-intestinal toxicity, and were thus less likely to have received the full dose of treatment.Although our trials did not include treatment with monoclonal antibodies, recent pharmacokinetic data showed that the clearance of rituximab is reduced and its elimination half-life more prolonged in women than in men. 20 Higher rituximab serum concentrations before next therapy and higher response rates were associated, in another pharmacokinetic study, 21 with female sex.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In another study, Xie et al showed that the CYP2B6*6 variant enhanced cyclophosphamide hydroxylation [34]. Lamba et al evaluated CYP2B6 splicing variants in human liver samples and demonstrated that the CYP2B6-G516T, -C1459T, and intron 3 C15582T genotypes were predictors of hepatic CYP2B6 activity and varied according to sex and ethnicity [35]. In an additional study by Desta et al, bupropion protein expression and activity, and EFV hydroxylation were significantly decreased in subjects with the CYP2B6*5, or CYP2B6*6 [26].…”
Section: Cyp2b6 Gene Polymorphisms and Hepatic Cyp2b6 Expression And mentioning
confidence: 99%
“…30 Alleles that carry polymorphisms 415A4G, 516G4T, 136A4G, 296G4A, 785A4G, 419G4A, and 1172T4A have all been associated with differences in the expression of the encoded proteins. [31][32][33] The relevance of CYP2B6 polymorphisms on EFV metabolism has been extensively analysed. Haas et al assessed the impact of the 526G4T polymorphism on EFV clearance Figure 2 Metabolic pathway for Efavirenz.…”
Section: Non-nucleoside Reverse Transcriptase Inhibitorsmentioning
confidence: 99%